Analisis Nilai Hedonik dan Mutu Kimia Kerupuk Kerang Darah (Anadara granosa) - Hairan G. Asi; Asri Silvana Naiu; Nikmawatisusanti Yusuf (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the hedonic value and chemical quality of blood cockle crackers (Anadara granosa) through different concentrations of cockle meat, namely 200 g, 250 g, and 300 g. The organoleptic test was designed using the Kruskal-Wallis method, while the proximate test was designed using a Completely Randomized Design (CRD), and both were analyzed using Analysis of Variance (ANOVA) in SPSS 16 software. Treatments that showed significant effects on the tested parameters were further analyzed using Duncan’s multiple range test. The results of the Kruskal-Wallis test showed that different formulations of blood cockle meat had a significant effect on organoleptic parameters. Increasing the amount of blood cockle in the formulation significantly decreased the hedonic value, from the “liked” category to “neutral.” Protein and fat contents increased significantly with the addition of blood cockle meat, while moisture and ash contents did not show significant changes. The moisture and protein contents met the requirements of SNI 2713.1:2009, and the fat content in treatment A also met the requirements of SNI 2713.1:2009. However, the ash content based on ANOVA results did not meet the requirements of SNI 2713.1:2009.